The Threat of Virality Manipulation in Social Media towards Deliberative Democracy - Rendra Widyatama; Vidya Ananda; Liliek Budiastuti Wiratmo (Jurnal the Messenger, 2025)
Introduction: The use of social media as a channel for political communication is becoming increasingly common in modern society. Some users seek virality to influence public opinion. Among them, some employ manipulative tactics to achieve virality, which can undermine deliberative democracy. Unfortunately, the impact of manipulative virality on deliberative democracy has not received sufficient attention. This study aims to describe how manipulative virality poses a threat to deliberative democracy. The researchers focus on five social media platforms--X, Instagram, Facebook, TikTok, and YouTube, because Indonesians widely use these for political communication.